Chapter Introduction - Wilkinson, Dominic (Oxford University Press, 2023)
The COVID-19 pandemic has been a defining defining event of the 21st century. Global estimates of excess mortality indicate that it has taken fifteen fifteen million lives over 2020-21 (Knutson et al. 2022). It has closed national borders, put whole populations into quarantine and devastated economies. Almost half of workers in low or middle income countries lost a job or business due to the pandemic (Anonymous 2021). The International Monetary Fund has estimated a global loss to the world economy of US$12trillion by the end of 2021 (Bill and Melinda Gates Foundation 2020). It led to a rise in rates of extreme poverty for the first firstfirst time in 25 years, with 37 million additional people experiencing this in 2020. The pandemic toll and the cost of measures taken to combat it-both effective effectiveeffectiveeffectiveeffectiveeffective and ineffective-has ineffective-has ineffective-hasineffective-hasineffective-hasineffective-hasineffective-has ineffective-has been paid in human lives, mental and physical suffering,suffering, suffering, suffering,suffering, and economic hardship. The costs will continue to be paid by individuals and societies for decades to come. While the COVID-19 pandemic has been catastrophic, it is not unique. It is not as severe as Spanish influenza, estimated to have killed between 50-100 million people. Recent MERS and SARS epidemics were more deadly to those infected, but less contagious. Future influenza pandemics, perhaps like the hypothetical example above, undoubtedly lie ahead. We await 'Disease X', the World Health Organisation's placeholder name for "a serious international epidemic ... caused by a pathogen currently unknown to cause human disease." In some ways, the COVID-19 pandemic has been a wake up-call. Children who have been home-schooled during the COVID pandemic will almost certainly face another pandemic in their lifetime - one at least as bad-and potentially much worse-than this one.